2002
DOI: 10.1080/1028602021000049087
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic compounds from the leaves of Koelreuteria paniculata Laxm

Abstract: From the fresh leaves of Koelreuteria paniculata Laxm (Sapindaceae), four new compounds, named ethyl p-trigallate (1), 3''-O-galloyl-4'-O-galloyl-4-O-galloyl-gallic acid (2), ethyl p-heptagallate (3) and 3''-galloylquercitrin (4), together with 12 known compounds namely catechin (5), galloylepicatechin (6), isorhamnetin (7), kaempferol-3-O-arabinopyranoside (8), quercetin-3'-O-beta-D-arabinopyranoside (9), quercitrin (10), methyl p-digallate (11), methyl m-digallate (12), p-digalloyl acid (13), m-digalloyl aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…The 2 C 28 H 24 O 15 isomers had analogous UV absorption peaks to compound 2, and had exactly 1 more gallic‐acid moiety, respectively; therefore, they are possibly gallic‐acid derivates from compound 2. Database searching with the molecular formulas and UV‐absorption peaks indicated that the 2 molecules were possibly 2″‐O‐Galloylquercitrin (compound 6) and 3″‐O‐Galloylquercitrin (compound 7) that were reported from medicinal plants Polygonum filiforme and Koelreuteria paniculata (Lin and others 2002). …”
Section: Resultsmentioning
confidence: 99%
“…The 2 C 28 H 24 O 15 isomers had analogous UV absorption peaks to compound 2, and had exactly 1 more gallic‐acid moiety, respectively; therefore, they are possibly gallic‐acid derivates from compound 2. Database searching with the molecular formulas and UV‐absorption peaks indicated that the 2 molecules were possibly 2″‐O‐Galloylquercitrin (compound 6) and 3″‐O‐Galloylquercitrin (compound 7) that were reported from medicinal plants Polygonum filiforme and Koelreuteria paniculata (Lin and others 2002). …”
Section: Resultsmentioning
confidence: 99%
“…30 (1H, dd, J = 1.6 Hz, H-6') showed o-coupled protons on ring B, while the signal at δ 7.35 (1H, d, J = 1.6 Hz, H-2') exhibited m-coupled, all of an ABC system, characteristic of 3', 4'-substituted ring B. (Bombardelli et al, 1973;Lin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Bulked fraction C gave quercitrin which showed less antibacterial activity with the MIC value of 50 µg/ml. Quercitrin has been isolated from plants, such as Piliostigma thonningii (Ibewuike, 1997;Bombardelli et al, 1973), Koelreuteria paniculata (Lin et al, 2002) and Hypericum caprifoliatum (Dall et al, 2003), and its antimicrobial activity widely reported in such plants.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 4-14 were identified by using 1 H NMR, 13 C NMR, DEPT-135, HMQC and HMBC as well as HRESIMS experiments, as: 5- O -methyl-luteolin 4 (Abou-Zaid et al, 2001), loliolide 5 (Kimura and Maki, 2002), kaempferol 7- O -α- l -rhamnoside 6 (Chua et al, 2008), kaempferol-3- O -α- l -rhamnoside (Afzelin) 7 (Cheng et al, 2013), methyl myo-inositol (Quebrachitol) 8 (HuiCong et al, 2013), β-sitosterol 9 (Lu et al, 2012), β-sitosterol-β- d -glucoside 10 (Wei et al, 2011), palmitic acid monoglyceride 11, ethyl gallate 12 (Yang et al, 1999), methyl gallate 13 (Lin et al, 2002) and gallic acid 14 (Qu et al, 2011). Compounds 4-6 were reported to be isolated for the first time from family Sapindaceae.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely distributed in Northern China. Local people use the seeds as insecticides and the leaves as antifungal and antibacterial agents (Lin et al, 2002). Recent reports showed that the crude extracts of this plant possessed antitumor and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%